Penurunan Glukosa dan Perubahan Profil Lipida Serum Tikus Sprague- Dawley Hiperglikemia-Hiperkolesterolemia Akibat Asupan Sorbitol-Oleat Poliester (SOPE) - Agnes Murdiati; Hastari Wuryastuty; Y. Marsono; Eni Harmayani (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2009)
Disorder of carbohydrate metabolism in the Diabetes Mellitus patients resulted in increasing of cholesterol synthesis. This condition increases the risk of heart attack or coronary heart disease, therefore it is recommended to lower fat intake. One of the alternatif to lower fat intake is by replacing fat with fat replacer in the diet. The aim of the present study is to evaluate the effect of replacing 75% of fat with SOPE on the glucose and lipid profile in diabetic-hipercholesterolemic rats. Eihgteen Sprague Dawley rats were devided into 2 groups of 9 rats. They were fed with hipercholesterol diet and were diabetic induced with alloxan IM injection. One group was fed with 75% SOPE substitute the fat in the standard diet and the other group was fed with standard diet. The result indicates that the oil substitution of standard diet of Sprague Dawley rats for sorbitol-oleic polyester as much as 75% gives an advantage to rats which suffer hiperglikemic-hypercholesterolemic because it decreased the glucose, total cholesterol, LDL cholesterol, and LDL/HDL cholesterol ratio, and did not decrease the HDL cholesterol, but increased triglyceride serum.